Variations in avoidable hospital admissions and emergency visits by primary care characteristics: an ecological study in Italy - Dalla Valle, Zeno; Ricciardi, Giovanni Emanuele; Signorelli, Carlo; Renzi, Cristina (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. Primary healthcare plays a central role in providing preventive care, managing chronic conditions and reducing inappropriate emergency presentations. The study aimed at providing population-level evidence on the correlation between the characteristics of primary healthcare across Italian regions and health outcomes included in the National Programs Outcomes of the National Agency for Regional Healthcare Services. Study Design. Ecological studyMethods. We analysed healthcare data from the National Agency for Regional Healthcare Services, the public lists of primary care doctors and the National Federation of Surgeons and Dentists and the National Institutes of Statistics referring to the 20 Italian regions. Pearson’s correlation and Spearman’s correlation were used to assess the relationships between primary healthcare characteristics and health outcomes.Results. Overall, across all Italian regions each general practitioner had on average 1447 patients and was 57.5 years old. The study found positive correlations between the number of patients per general practitioner and non-urgent Emergency Department visits among adult patients (Pearson’s r = 0.58, p = 0.008), the number of residents aged 65+ per general practitioner and the rate of chronic obstructive pulmonary disease admissions (Pearson’s r = 0.49, p = 0.029), and the age of general practitioners and lower-extremity amputations in diabetes patients (Pearson’s r = 0.56, p = 0.011). A negative correlation was observed between the age of general practitioners and urinary tract infection admissions (Pearson’s r = -0.76; p < 0.001). A non-linear negative correlation was found between the age of general practitioners and chronic obstructive pulmonary disease admissions (Spearman’s ρ = -0.46, p = 0.041).Conclusions. The findings emphasise the importance of guaranteeing sufficient numbers of primary healthcare physicians to meet patients’ needs, and for limiting avoidable hospitalisations and emergency presentations. General practitioners’ age might also influence the provision of care, but more research is needed on possible mechanisms.